PENGARUH KONFLIK KERJA, REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN - Tri Rahayu Ramadani; Evi Marlina; Siti Rodiah (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2023)
This study aims to examine the effect of work conflict, reward and punishment on the performance of Cinter Stationery employees. This research uses a type of quantitative descriptive research. The population in this study are all employees who work at Cinter Stationery. The sampling method in this study used a non-probability sampling technique, namely saturated sampling with a total of 87 respondents. The data collection technique used was a questionnaire. The data analysis technique used is multiple linear regression analysis method. The results of the study show that work conflict has a significant effect on employee performance, reward has an effect on employee performance and punishment has an effect on Cinter Stationery employee performance.